The Political Economy of Social Protection in Mozambique - Buur, Lars; Salimo, Padil (SSRN Electronic Journal, 2018)
In the view of international donors, multilateral organisations and government officials, social protection in Mozambique benefits from strong government commitment to it. Their argument is that, in contrast to many African countries, the government has demonstrated a level of commitment and support to social protection that is quite unprecedented. This view relies on the fact that more than 90 per cent of the budget allocated to the implementation of social protection programmes comes from the state budget and that, even within the complex context of the financial crisis that has devastated the economy since 2013, social protection has continued to receive special attention from the government in its budget allocations. Based on a political economy analysis, this paper challenges the common narrative of social protection in Mozambique, by arguing that social protection has been used as a means to mobilise resources from international agencies, in order to ensure the political survival of the Frelimo government. The paper argues that government support of social protection emerged as a reaction to the poor performance of poverty-reduction initiatives, becoming also a mechanism to overcome social protests after the 2008 and 2010 riots in Mozambique, which threatened to jeopardise the stability of the regime and its reproduction of power.
Keywords: *indexed; *tagged; Ethnographic Studies; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Social Protection PEA; development partners / parceiros de cooperação; social protection / proteção social